2019
DOI: 10.1101/713602
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of maternal prenatal psychological stressors and distress with maternal and early infant faecal bacterial profile

Abstract: BackgroundFindings from animal studies indicate that the early gut bacteriome is a potential mechanism linking maternal prenatal stress with health trajectories in offspring. However, clinical studies are scarce and the associations of maternal psychological profiles with the early infant faecal bacteriome is unknown. This study aimed to investigate the associations of prenatal stressors and distress with early infant faecal bacterial profiles in a South African birth cohort study.MethodsAssociations between p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…There is evidence to confirm that the family Brachyspiraceae and Peptostreptococcaceae are associated with intestinal bacterial infection 57,58 . Fecal specimens from mothers exposed to intimate partner violence have lower proportions of Peptostreptococcaceae at birth 59 . This finding provides insight into the involvement of the gut bacteria linking maternal psychological adversity and the maturing infant brain.…”
Section: Discussionmentioning
confidence: 97%
“…There is evidence to confirm that the family Brachyspiraceae and Peptostreptococcaceae are associated with intestinal bacterial infection 57,58 . Fecal specimens from mothers exposed to intimate partner violence have lower proportions of Peptostreptococcaceae at birth 59 . This finding provides insight into the involvement of the gut bacteria linking maternal psychological adversity and the maturing infant brain.…”
Section: Discussionmentioning
confidence: 97%
“…Infants exposed to prenatal stress have also been shown to have increased levels of Firmicutes (Weissella) and Enterobacteriaceae (unclassified genera) in the meconium [105], the latter of which has been found to be characteristic of depression in later life [106]. Animal studies have also found similar results, whereby prenatally stressed monkey infants were seen to have an altered microbiota composition compared to control infants, with significantly lower levels of lactobacilli and bifidobacteria [107].…”
Section: Prenatal Stressmentioning
confidence: 88%